HUBUNGAN INTERPERSONAL DALAM PENGADAAN BAHAN PUSTAKA: STUDI KASUS DI PERPUSTAKAAN UIN SUNAN KALIJAGA - Nor’Aini Hadna, Ida (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2013)
This study aims to perceive the efforts done by State Islamic University (UIN) Sunan Kalijaga in running the literature acquisition process. It relates to the main task of library to fulfill the needs of the academicians’ learning process. In addition, the acquisition process is complicated and involves various parties namely lecturers, students, finance division, supplies division, faculties, distributors, vendors, publishers, and the librarians themselves. This study used qualitative method with interview techniques. The results showed that to expedite the work in literature acquisition, librarians must have interpersonal relationship with many parties like lecturers, students, faculties, publishers, distributors, supplies division and finance division.